1997
DOI: 10.1002/chin.199751315
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Active Sites in Pt‐Mo on Silica Catalysts for Reactions of Hydrocarbons with Hydrogen

Abstract: Active Sites in Pt-Mo on Silica Catalysts for Reactions of Hydrocarbons with Hydrogen -(60 refs.). -(LECLERCQ, G.; PIETRZYK, S.; ROMERO, T.; EL GHARBI, A.; GENGEMBRE, L.; GRIMBLOT, J.; AIESSI, F.; GUELTON, M.; LATEF, A.; LECLERCQ, L.; Ind. Eng.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
2
0
1
Order By: Relevance
“…The binding energy for Mo(3d 5/2 ) and Mo(3d 3/2 ) showed some slight variation with different samples, but dropped to 227.8-228.2 and 230.7-231.1 eV, respectively; that for C(1s) dropped to 283.8 eV. These values are consistent with those attributed to Mo 2 C [28,29]. In terms of the acidity of the catalysts, we refer to our previous work, which used the same samples [30].…”
Section: Methodssupporting
confidence: 90%
“…The binding energy for Mo(3d 5/2 ) and Mo(3d 3/2 ) showed some slight variation with different samples, but dropped to 227.8-228.2 and 230.7-231.1 eV, respectively; that for C(1s) dropped to 283.8 eV. These values are consistent with those attributed to Mo 2 C [28,29]. In terms of the acidity of the catalysts, we refer to our previous work, which used the same samples [30].…”
Section: Methodssupporting
confidence: 90%
“…So far, a few approaches are available for the synthesis of molybdenum carbide nanostructures. Most of these methods are connected to reductive carburization of molybdenum oxide particles in the CH 4 –H 2 mixture, including temperature‐programmed reaction and CVD, pyrolysis of metal complexes, liquid‐phase reaction, template method, etc. One of the most common methods is the temperature‐programmed reduction (TPR) of the molybdenum oxide by gaseous hydrocarbons, as pioneered by Levy and Boudart.…”
Section: Synthesis Methods For Transition Metal Carbides and Nitridesmentioning
confidence: 99%
“…Since Levy and Boudart demonstrated that tungsten carbide (WC) exhibited catalytic activity similar to Pt [1], metal carbide based catalysts have attracted a significant amount of attention due to their catalytic similarity to noble metal catalysts [2][3][4][5]. Along with WC, molybdenum carbide (Mo 2 C) catalysts have been one of the primary carbides studied, particularly for reactions involving hydrocarbons [6][7][8][9][10][11]. After Green and coworkers demonstrated that WC and Mo 2 C catalyzed methane reforming reactions with activities comparable to Ir and Ru [12][13][14][15][16][17], studies of methane and hydrocarbon reforming catalyzed by Mo 2 C have become a popular vein of research [18][19][20].…”
Section: Introductionmentioning
confidence: 99%